Functional magnetic resonance imaging of recovery from post-stroke aphasia - Bethel, Susannah (2009)
This thesis presents the design, development and application of a novel overt picture-naming paradigm through a series of exploratory behavioural and imaging experiments. The paradigm is subsequently used in a functional magnetic resonance imaging study of recovery from post-stroke aphasia. The possibility of comparing correct and error naming responses in aphasic patients and unimpaired subjects induced to make errors was investigated and successfully trialled. This research improves on techniques currently favoured in imaging studies to explore the processes involved in functional recovery in a more analytical way. The novel study design provides a new way to interrogate processing involved in the production of aphasic responses.